FLUIDIZATION OF A BED OF SOLID PARTICLES IN A TWO DIMENSIONAL VERTICAL BOX - Aufa Numan Fadhilah Rudiawan; Kurnia Novita Sari; Hirofumi Notsu; Sparisoma Viridi (Spektra: Jurnal Fisika dan Aplikasinya, 2019)
Simulation of fluidization of a bed of solid particles in a two-dimensional box is performed using molecular dynamics methods by assuming that superposition of buoyant, gravitational, viscous, collision force will make the particle to move in two dimensions. Two different fluid type is used in this simulation, i.e., gas and liquid fluid. By increasing the fluid velocity from small to high, then minimum fluidization condition reached. As a result, fluidization of alumina particle with liquid fluid has a minimum fluidization velocity lower than gas fluid.